COMPARISON OF THE MOST PROFITABLE INVESTMENT OPTIONS AMONG BITCOIN, LQ45 STOCKS, AND GOLD IN A PERIOD OF 10 YEARS (2011-2021) - Silaban, Jonathan Phelipe (TEMA, 2022)
The objective of this study is to empirically assess the efficiency of investment between bitcoin, LQ45 stocks, and gold through significant the returns and risks among the variables. This investment efficiency attracts many people, especially young people and people who understand technology. This time, researchers try to find out which kind of investment offers the most significant profit and lesser risk in ten years to help people choose the best type of investment that suits them. Because many people from any generation are eager to learn about investing. Based on the previous research, turns out that bitcoin is the best investment tool compare to other investment instruments even it has bigger risk. the data used in this study collected from website in the internet, investing.com. According to the historical data from the most complete stock and commodities price website in the internet, investing.com, the writer tried to measure the return and risk from a period of 10 years (2011-2021). The result is Bitcoin has the biggest return than other instrument, but also having the highest risk than Gold and LQ45 Stock